2016
DOI: 10.1002/jhbp.368
|View full text |Cite
|
Sign up to set email alerts
|

Adverse oncologic effects of intraoperative transfusion during pancreatectomy for left-sided pancreatic cancer: the need for strict transfusion policy

Abstract: Intraoperative transfusion should be avoided by gentle operative handling to minimize intraoperative bleeding, and the appropriate transfusion policy should be followed to increase the survival outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…This is reflected by beneficial survival data for individual indications, which were also in good agreement with data in the literature: Jarnagin et al (intrahepatic and perihilar cholangiocarcinoma, 63 and 69% [ 17 ]; Zaydfudim et al (hepatocellular carcinoma, 6059 [ 18 ]; Schiergens et al and Margonis et al (CRLM 68% with transfusion and 82% without transfusion) [ 15 , 19 ]; esophageal cancer (40% with transfusion vs. 60% without transfusion) [ 20 ]; gastric cancer (82 vs. 60%) [ 16 ]; and pancreatic cancer (50 to 60% vs. 20%) [ 13 , 21 ]. Last not least, Mörner et al showed that anemia and transfusions were associated with adverse outcome [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected by beneficial survival data for individual indications, which were also in good agreement with data in the literature: Jarnagin et al (intrahepatic and perihilar cholangiocarcinoma, 63 and 69% [ 17 ]; Zaydfudim et al (hepatocellular carcinoma, 6059 [ 18 ]; Schiergens et al and Margonis et al (CRLM 68% with transfusion and 82% without transfusion) [ 15 , 19 ]; esophageal cancer (40% with transfusion vs. 60% without transfusion) [ 20 ]; gastric cancer (82 vs. 60%) [ 16 ]; and pancreatic cancer (50 to 60% vs. 20%) [ 13 , 21 ]. Last not least, Mörner et al showed that anemia and transfusions were associated with adverse outcome [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the results from the present study. Furthermore, intraoperative transfusion, lymph node metastasis and lymph node ratio have been reported as independent prognostic factors in predicting tumor recurrence (54). However, how intraoperative transfusion may have a negative impact on the recurrence and OS of patients with cancer remains unclear.…”
Section: -Year Os 3-year Os 5-year Os ------------------------------mentioning
confidence: 99%
“…Factors such as availability of combined resection, operation time, amount of blood loss, and availability of transfusion are decided at the time of surgery and could play a role in improving survival and recurrence rates of patients who undergo pancreatectomy. Of these factors, we focused on transfusion and their inappropriate performance during pancreatectomy and hypothesized that reduction of such inappropriate transfusions could improve patient outcomes [7]. Given that the interactions of the host immune system and cancer microenvironment play an important role in determining outcome, and the fact that transfusion lowers a patient's immunity and aggravates outcome [8,9], we concluded that intraoperative transfusion (IOT) might lead to poor outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Most, however, focus on the effect of IOT on recurrence and survival in pancreaticoduodenectomy cases and not in other types of pancreatectomy, because of the complicated procedure of pancreaticoduodenectomy [10][11][12]. One particular study suggests that transfusion performed during pancreatectomy for left-sided pancreatic cancer patients is harmful [7]. While that study focused on more than just pancreaticoduodenectomy, it involved a small number of subjects and focused only on left-sided pancreatic cancer; therefore, it is unlikely to provide a strong guideline against transfusion during pancreatic cancer surgery.…”
Section: Introductionmentioning
confidence: 99%